Alternative BCG delivery strategies improve protection against Mycobacterium tuberculosis in non-human primates: Protection associated with mycobacterial antigen-specific CD4 effector memory T-cell populations. (December 2016) - Sharpe, S.; White, A.; Sarfas, C.; Sibley, L.; Gleeson, F.; McIntyre, A.; Basaraba, R.; Clark, S.; Hall, G.; Rayner, E.; Williams, A.; Marsh, P.D.; et al.
Abstract: Intradermal (ID) BCG injection provides incomplete protection against TB in humans and experimental models. Alternative BCG vaccination strategies may improve protection in model species, including rhesus macaques. This study compares the immunogenicity and efficacy of BCG administered by ID and intravenous (IV) injection, or as an intratracheal mucosal boost (ID + IT), against aerosol challenge with Mycobacterium tuberculosis Erdman strain. Disease pathology was significantly reduced, and survival improved, by each BCG vaccination strategy, relative to unvaccinated animals. However, IV induced protection surpassed that achieved by all other routes, providing an opportunity to explore protective immunological mechanisms using antigen-specific IFN-γ ELISpot and polychromatic flow cytometry assays. IFN-γ spot forming units and multifunctional CD4 T-cell frequencies increased significantly following each vaccination regimen and were greatest following IV immunisation. Vaccine-induced multifunctional CD4 T-cells producing IFN-γ and TNF-α were associated with reduced disease pathology following subsequent M.tb challenge; however, high frequencies of this population following M.tb infection correlated with increased pathology. Cytokine producing T-cells primarily occupied the CD4 transitional effector memory phenotype, implicating this population as central to the mycobacterial response, potentially contributing to the stringent control observed in IV vaccinated animals. This study demonstrates the protective efficacy of IV BCG vaccination in rhesus macaques, offering a valuable tool for the interrogation of immunological mechanisms and potential correlates of protection.